Adaptive torque tracking control during slip engagement of a dry clutch in vehicle powertrain. (April 2019) - Park, Jinrak; Choi, Seibum; Oh, Jiwon; Eo, Jeongsoo
Highlights: An adaptive torque tracking control method during slip engagement of a dry clutch in a vehicle powertrain is developed. The proposed method is applied to the slip engagement control of an engine clutch in a parallel hybrid vehicle. The proposed method is verified with production vehicle experiments. Feedforward control based on a clutch friction model is performed for the slip engagement control. The forward path torque estimator of an engine clutch in the driveline is utilized to adapt the clutch friction model. Abstract: Dry clutches have been gaining its popularity for use in the transmission systems of small and medium-sized vehicles as well as the engine clutch systems of parallel hybrid vehicles. With this trend, the ability to appropriately control the amount of torque transferred through the dry clutch becomes important. This paper addresses a feedforward control method of clutch torque during slip engagement of a dry clutch utilizing a clutch friction model. In many studies, the clutch friction coefficient is considered as the only uncertain parameter in the clutch friction model. However, the clutch touch point can also serve as a major source of uncertainty in the clutch friction model. Thus, this paper proposes a simultaneous adaptation method to estimate the clutch friction coefficient and the clutch touch point in real time and a feedforward control method of clutch torque during slip engagement of a dry clutch based on the proposed adaptation algorithm. This control approach is applied to the slip engagement control of a dry engine clutch in a parallel hybrid vehicle and its effect is experimentally verified using a production vehicle.